PERBANDINGAN SISTEM HUKUM INDONESIA DAN MALAYSIA TENTANG PASAR MODAL - Gultom, Elfrida Ratnawati; Siswanto, Andrew Stevie (Ensiklopedia of Journal, 2024)
Abstract: The capital market is the main weapon for every country in driving the national economy, especially for developing countries such as Indonesia and Malaysia. However, in these two countries, differences in capital market development are clearly visible from the annual gross domestic product per capita. Indonesia, as a vast country with abundant natural resources, should have a stock market that is actually better than Malaysia, but on the contrary, Indonesia is actually below Malaysia. So the first problem is formulated, do the legal rules regarding capital markets regulated in Indonesia have similarities/differences with other countries, especially Malaysia?, and secondly, what are the factors that cause similarities and/or differences in the legal systems between Indonesia and Malaysia in regulating capital markets of each country? The research method used is a normative juridical research method which is equipped with a conceptual approach and a statutory approach. So the first result was obtained, that according to Lawrence Friedman there are several things that indicate similarities or differences in capital market legal regulations, including those that can be seen from the historical, cultural and anthropological perspective contained in each draft law formation. The second result is that according to Peter de Cruz, comparative law can be viewed from legal institutions, legal sources and legal development, but there are exceptions in legal institutions because they have many similarities, while the other two are differences between the two countries.Keywords: Comparative Law, Indonesia, Capital Market